The changing energy mix : a systematic comparison of renewable and nonrenewable energy - Meier, Paul F. (Oxford University Press, 2020)
"The energy mix is changing, and renewable energy is growing in importance. If you were born before 1989, you lived in a U.S. where there was no electricity generated from either wind or solar power and very little from geothermal and biomass. Now, in 2018, the combined generation from wind and solar has surpassed hydroelectricity. Fourteen states now generate more than 10% of their electricity from wind and three generate more than 30%. And bioethanol, produced from corn grain, now makes up 10% of the U.S. gasoline market. Changes have also occurred in the nonrenewable energy mix. Coal, which was responsible for 53% of the U.S. electricity generation in 1998 is now only 28%, as natural gas has taken the leadership role, surpassing coal in 2015 as the primary energy for producing electricity. Similarly, the world did not see any electricity generation from wind until 1985 and none from solar until 1989. Now solar plus wind generate 7% of the worldwide electricity. The worldwide demand for all energy types is also increasing rapidly, as energy usage has increased 84% over the last twenty years. This book makes a systematic comparison of twelve different energy types to help understand the driving forces for this changing energy mix. Twelve common criteria are used to provide tools to make these comparisons, such as proven reserves, the levelized cost for each energy type, energy balances, environmental issues, and the energy footprint. Proven reserves are also projected for each renewable energy type"-- Provided by publisher.
Keywords: Power resources -- United States.; Renewable energy sources -- United States.; elektronické knihy; electronic books